Orange juice processing using a continuous flow ultrasound-assisted supercritical CO2 system: Microbiota inactivation and product quality. (June 2018) - Paniagua-Martínez, I.; Mulet, A.; García-Alvarado, M.A.; Benedito, J.
Abstract: The feasibility of using supercritical CO2 assisted by ultrasound (SC-CO2 -HPU) in continuous mode (3.06 min residence time) for the non-thermal pasteurization of orange juice was evaluated. The proposed technology was effective for microbial inactivation; complete inactivation was obtained for E . coli and total aerobic mesophilic bacteria while 99.7% reduction for S . cerevisiae . Results showed that the SC-CO2 -HPU treatment brought about small changes in the pH, °Brix and titratable acidity of the juice. Furthermore, although SC-CO2 -HPU technology produced a higher browning index (211%) and greater changes in color, it was possible to improve the cloud of juice by 173%; what is more, a smaller percentage of phenolic compounds (6.5%) and ascorbic acid (5.5%) was lost compared to the thermally pasteurized juice (10% decrease in both parameters). Moreover, the antioxidant capacity could be increased (12%) with respect to the natural juice. Therefore, SC-CO2 -HPU technology appears to be effective for microbial pasteurization and the mild process conditions used could lead to an increase in the juice quality. Industrial relevance: The demand for high quality processed foods which preserve their natural and fresh-like characteristics has awakened a growing interest in non-thermal technologies. The ultrasound-assisted SC-CO2 continuous system is an innovative non-thermal technology that could represent a development in the area of emerging technologies. This technology allows high quality products to be obtained by preserving their natural bioactive compound content while maintaining their fresh-like organoleptic characteristics. In fact, food experts working in academia, industry or governmental agencies worldwide foresee that non-thermal emerging technologies will be among the most impactful novel food processing technologies for the next decade in terms of product commercialization. Highlights: Ultrasound-assisted continuous SC-CO2 reduced the orange juice microbiota. The treatment produced greater changes in color (darkening) than thermal pasteurization. The cloud of the treated juice and the phenolic and vitamin contents were improved by 173%, 6.5% and 5.5%, respectively. The antioxidant capacity of the treated juice increased with respect to the fresh (untreated) one. Ultrasound intensification may improve the acceptance of SC-CO2 processing by the food industry.